Neuroinflammation Induced by Surgery Does Not Impair the Reference Memory of Young Adult Mice - Yanhua Zhao; Lili Huang; Huan Xu; Guangxi Wu; Mengyi Zhu; Jie Tian; Hao Wang; Xiangrui Wang; Weifeng Yu; Liqun Yang; Diansan Su (Mediators of Inflammation)
Postoperative cognitive dysfunction (POCD) increases morbidity and mortality after surgery. But the underlying mechanism is not clear yet. While age is now accepted as the top one risk factor for POCD, results from studies investigating postoperative cognitive functions in adults have been controversial, and data about the very young adult individuals are lacking. The present study investigated the spatial reference memory, IL-1β, IL-6, and microglia activation changes in the hippocampus in 2-month-old mice after anesthesia and surgery. We found that hippocampal IL-1β and IL-6 increased at 6 hours after surgery. Microglia were profoundly activated in the hippocampus 6 to 24 hours after surgery. However, no significant behavior changes were found in these mice. These results indicate that although anesthesia and surgery led to neuroinflammation, the latter was insufficient to impair the spatial reference memory of young adult mice.